2008
DOI: 10.1136/bmj.a2494
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Parkinson's disease after hospital contact for head injury: population based case-control study

Abstract: Objective To determine whether a hospital contact for a head injury increases the risk of subsequently developing Parkinson’s disease.Design Population based case-control study.Setting Denmark.Participants 13 695 patients with a primary diagnosis of Parkinson’s disease in the Danish national hospital register during 1986-2006, each matched on age and sex to five population controls selected at random from inhabitants in Denmark alive at the date of the patient’s diagnosis (n=68 445).Main outcome measures Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
112
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(121 citation statements)
references
References 25 publications
6
112
1
Order By: Relevance
“…This study reported increased risk of PD following head trauma (OR 1.5, 95% CI 1.4-1.7), but the increase was almost entirely due to trauma that occurred during the three months before first hospital contact due to PD (OR 8.0, 95% CI 5.6-11.6). Head trauma that occurred between 4 months and 9 years before first hospital contact due to PD only slightly increased risk of PD (OR 1.5, 95% CI 1.3-1.7), and for traumas that occurred 10 years or more before, there was no association (OR 1.1, 95% CI 0.9-1.3) [627]. The authors interpreted these results as being due to reverse causation [627].…”
Section: Head Traumamentioning
confidence: 96%
See 3 more Smart Citations
“…This study reported increased risk of PD following head trauma (OR 1.5, 95% CI 1.4-1.7), but the increase was almost entirely due to trauma that occurred during the three months before first hospital contact due to PD (OR 8.0, 95% CI 5.6-11.6). Head trauma that occurred between 4 months and 9 years before first hospital contact due to PD only slightly increased risk of PD (OR 1.5, 95% CI 1.3-1.7), and for traumas that occurred 10 years or more before, there was no association (OR 1.1, 95% CI 0.9-1.3) [627]. The authors interpreted these results as being due to reverse causation [627].…”
Section: Head Traumamentioning
confidence: 96%
“…Head trauma that occurred between 4 months and 9 years before first hospital contact due to PD only slightly increased risk of PD (OR 1.5, 95% CI 1.3-1.7), and for traumas that occurred 10 years or more before, there was no association (OR 1.1, 95% CI 0.9-1.3) [627]. The authors interpreted these results as being due to reverse causation [627].…”
Section: Head Traumamentioning
confidence: 96%
See 2 more Smart Citations
“…We confined our risk factor assessment to 19 demographic, genetic, or disease characteristics associated with DLB, AD, or PD and for which data were available from the studies: age, 5 sex, 5 family history of dementia 2,7,8 or PD, 9,10 APOE e4 status (any e4 alleles vs none), 11,12 history of anxiety 13 or depression, 14,15 smoking (ever vs never in lifetime), 16,17 alcohol (ever vs never) 18,19 and caffeine consumption (ever vs never), 20,21 cancer (excluding nonmelanoma skin cancer), 22,23 diabetes mellitus, 24,25 education (9 or more years vs less than 9), 26,27 head injury, 28,29 number of children in men (more than one vs zero or one child), 30 occupation as a physician (vs all other occupations), 27 oophorectomy (uni-or bilateral, with or without hysterectomy), 31,32 oophorectomy at or before age 45, 32,33 and stroke. 34,35 Data definitions are in table e-1 on the Neurology ® Web site at www.neurology.org.…”
Section: Conclusion: Dlb Risk Factors Are An Amalgam Of Those For Ad mentioning
confidence: 99%